Customer perception on e-banking and assessing the online banking performance of Uttara Bank Ltd. - Zaman, Nawreen Fahmida (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.